Compared to Facebook, Instagram use causes more appearance comparison and lower body satisfaction in college women. (September 2020) - Engeln, Renee; Loach, Ryan; Imundo, Megan N.; Zola, Anne
Highlights: Spending seven minutes browsing Instagram decreased college women's body satisfaction. Compared to Facebook, women browsing Instagram made more appearance comparisons. Women using Instagram reported thinking about their appearance more than women using Facebook. Abstract: The current experiment tested the effect of social media use on college women's appearance comparisons, mood, and body satisfaction. We randomly assigned 308 undergraduate women (aged 18–26) to use Facebook, use Instagram, or play a matching game (the control condition) on an iPad for seven minutes. Compared to the Facebook condition, Instagram users retrospectively reported spending more time viewing images or videos containing people. Participants in both the Facebook and Instagram conditions also retrospectively reported engaging in more appearance comparisons relative to those in the control condition, but Instagram users reported significantly more appearance comparisons than those in the Facebook condition. Those who used Instagram, but not Facebook, showed decreased body satisfaction, decreased positive affect, and increased negative affect. Results are consistent with previous research suggesting social media use influences body satisfaction and social comparison, and that Instagram may be a particularly harmful platform when it comes to body image because of its focus on photos over text.